Successful coaching - Martens, Rainer (Human Kinetics, 2012)
This comprehensive text includes content on how to communicate and motivate players, as well as manage problem behaviors among athletes with a positive approach. It provides a full introduction to the games approach to coaching and strategic advice on how to incorporate this into a successful programme.